Розробка макета візуальної індикації параметрів автомобіля - Бездітко, А. Ю. (ХНУРЕ, 2021)
Visual indication of vehicle parameters is one of the most important sources of information for the driver of a vehicle, the safety and comfort of a car ride depends on its informativeness and accuracy of parameters. My project is to create a fully electronic dashboard that uses proprietary software and hardware to work inside the car in place of the standard dashboard. All data is displayed on a single screen. This option is considered more modern, the most convenient and informative. The work is based on the Arduino Mega microcontroller and LCD screen LQ123K1LG03, in a plastic case made of ABS plastic.
Keywords: параметри автомобіля; макет візуальної індикації